ANALISIS PERAN UNIT PELAKSANA TEKNIS DINAS PENGAWASAN KETENAGAKERJAAN KOTA BATAM TERHADAP PENGAWASAN UPAH MINIMUM KOTA BATAM - Nofriyanti, Aci; Lodan, Karol Teovani (SCIENTIA JOURNAL, 2019)
Debate about Regency /City Minimum Wages often results in demonstrations conducted by workers / laborers. Demonstrations that continue to recur every year on the same issue, clearly indicate that there are serious issues regarding wages. Wages play an important role and are one of the characteristics of an employment relationship, even wages are said to be one of the main goals of someone to do work for other people or legal entities. But in this case there are still some companies in the city of Batam that do not set wages in accordance with applicable regulations. The method used in this research is Qualitative-Descriptive, data collection techniques in the form of interviews and documentation which will later be processed into the discussion. The results of this study indicate that the supervisory process has been running but is not optimal because there are still many companies that do not know about the supervision carried out by the labor inspector due to the lack of human resources owned by the Technical Implementation Unit of the Manpower Supervision Office.